Clinical Application of the Peroneal Artery Perforator Flap for Reconstruction of Lateral Malleolus Defects. (June 2023) - Shih, Yu-Jen; Wang, Yen-Chun; Lin, Chin-Ta; Chang, Shun-Cheng; Tzeng, Yuan-Sheng; Dai, Niann-Tzyy; Chen, Tim-Mo; Wang, Chih-Hsin; Chen, Shyi-Gen
The reconstruction of defects of the lateral malleolus involving the exposed fibular bone or tendon is challenging. This study aimed to evaluate the clinical application of the peroneal artery perforator flap with or without split-thickness skin grafting for soft tissue reconstruction of the bony defect of the lateral malleolus of the ankle joints. Reconstruction using a peroneal artery perforator flap with or without split-thickness skin grafting was performed for 15 patients (10 men, 5 women) between January 2007 and December 2018. The mean age was 53.7 years, and the mean size of the flaps was 40 cm 2 . The flaps were elevated in the form of a perforator flap, and split-thickness skin grafting was performed over the flaps and adjoining raw areas. The flaps survived in all cases; however, partial necrosis was observed in 3 cases. In cases of small-sized defects of the lateral malleolus of the ankle joints where a flap is required for the exposed bone or tendon, reconstruction using the peroneal artery perforator flap is advantageous, since the morbidity rate of the donor site is low and soft tissue is reconstructed.